SURVEI INDEX MASA TUBUH DAN AKTIVITAS FISIK PADA SISWA MAMBUSAO NATIONAL HIGH SCHOOL - I Putu Bagus Wirasukmana; Ristanti Puji Astuti (Universitas Mercu Buana Yogyakarta, 2025)
This study aimed to describe Body Mass Index and physical activity levels as well as the effect of Body Mass Index on physical activity among students of class XII IPA 3 at Mambusao National High School. This study employed a quantitative descriptive method. The research subjects consisted of 34 students of class XII IPA 3. BMI was measured using the Body Mass Index formula based on World Health Organization (WHO) standards, while physical activity levels were assessed using the Global Physical Activity Questionnaire (GPAQ) WHO. The results showed that students’ BMI status consisted of 7 students classified as obesity level II, 3 students as obesity level I, 2 students at risk of obesity, 15 students with normal BMI, and 7 students classified as underweight. Meanwhile, physical activity levels were categorized as high in 24 students (70%), moderate in 5 students (15%), and low in 5 students (15%). Based on these findings, it can be concluded that the majority of students had a high level of physical activity despite variations in Body Mass Index. Therefore, continuous monitoring of nutritional status and promotion of physical activity are necessary to maintain students’ health.